Roadside Use of Native Plants - Harper Lore Bonnie L (Island Press, 2000)
Originally published by the U.S. Department of Transportation's Federal Highway Administration (FHWA), Office of Natural Environment to promote the planting and care of native plants along highway rights-of-way, this unique handbook provides managers of roadsides and adjacent lands with the information and background they need to make site-specific decisions about what kinds of native plants to use, and addresses basic techniques and misconceptions about using native plants. It brings together in a single volume a vast array of detailed information that has, until now, been scattered and difficult to find.